ANALISIS PENGARUH UKURAN PERUSAHAAN,PROFITABILITAS, DAN LEVERAGE TERHADAP PENGUNGKAPAN CSR DI BURSA EFEK INDONESIA - Martina Viviliana Ocin (ITB AAS Indonesia Surakarta, 2021)
The purpose of this study is to determine and analyze the effect of company size, profitability and leverage on disclosure of corporate social responsibility (CSR) in companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2015-2019. The data used is secondary data, while the data source is obtained through the site http://www.idx.co.id. Of the 49 listed mining companies, only 12 met the criteria for the research sample that had been determined. The data were analyzed by using the Classical Assumption Test, Hypothesis Testing using Multiple Linear Regression Analysis with the help of SPSS. The results show that simultaneously the variable company size, profitability and leverage have a significant effect on CSR disclosure in mining companies listed on the Indonesia Stock Exchange in 2015-2019. Partially, the firm size and leverage have a positive and significant effect on CSR disclosure, while the partial profitability variable does not have a positive and significant effect on CSR disclosure in mining companies listed on the Indonesia Stock Exchange. Keywords: Company Size; Profitability and Leverage; Liability Corporate Social Responsibility (CSR)